Numerical investigation on Re-oxygenation efficiency of stepped overflow weir in urban stream. (10th June 2020) - Dai, Zhaoxia; Zhang, Jiong; She, Rui; Hu, Nian; Xia, Shuang; Ma, Guodong; Han, Ruonan; Ming, Ruiping
Abstract: Dissolved oxygen concentration in water is one of the critical indicators for measuring the self-purification ability of water. The process of re-oxygenation directly affects the migration, diffusion, and degradation of organic pollutants in water as well as the self-purification process of an entire body of water. To solve the problem of water pollution and restore the ecological and social functions of the urban stream has become the key to ensure the sustainable development of the city. Many overflow weirs have been built along urban streams in northern China to retain landscape water. This study attempts to use a numerical simulation method to study the factors affecting the re-oxygenation process of urban streams by overflow weirs. Combined with flow regime analysis, the re-oxygenation efficiency of stepped overflow weirs for free surface flow under different influence factors such as unit discharge, number of steps and slope of overflow weir were compared. The results show that the re-oxygenation efficiency of a nappe flow is higher than that of a skimming flow or a transition flow. Re-oxygenation efficiency is sensitive to changes in unit discharge and reaches its peak value when the unit discharge of an inlet is about 0.06 m 2 /s. A comparison analysis of our present experimental simulation data shows that the slope for stepped overflow weirs for optimum re-oxygenation efficiency is 51.3°. For small flow conditions ( q  < 0.10 m 2 /s), stepped overflow weirs with fewer steps and greater weir height contribute to higher re-oxygenation efficiency. For large flow conditions ( q  > 0.10 m 2 /s), unit discharge, number of steps, and total weir height have little effect on the re-oxygenation efficiency of stepped overflow weirs. Graphical abstract: Image 106785 Highlights: Numerical simulation combining the VOF method, species transport model and UDF was conducted. Nappe flow regime provides a greater E 20 than that of the other flow regimes. The slope for stepped overflow weirs for optimum re-oxygenation efficiency is 51.3°. Stepped flow weirs with fewer steps and a greater height produce greater E 20 for q  < 0.10 m 2 /s.